(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Gen Z is the primary digitally local generation, born at the height of technical innovation. Younger adults are main the manner in expanded mobility, preferring laptops to computer systems and the use of their mobile telephones for a diffusion of functions, along with net, e mail, tune, video games, and video. In the present research primary data were collected by structured questionnaire from 100 respondents in Thoothukudi Town. The main objectivity of the study was to determine the factors influencing Gen Z preference towards gadgets . The collected data was analysed using simple percentage, Z test and ANOVA. The study concludes that most of the respondents prefer to use devices even as drowsing; they do now not have a time restrict in using the gadgets. Over usage of devices at some stage in night time outcomes in mistaken sound asleep, because of unsuitable snoozing their subsequent day work will no longer be carried out successfully. Dependancy of using gadgets in night time must be decreased. Students ought to be greater encouraged to spend time on bodily sports and outdoor video games. More research need to be carried out concerning this problem so as to cope with the problem more exactly and strengthen the strategies further for the close to future.